Logos and Sarx - Galloway, Allan D. (Toronto journal of theology, 2002)
"The Word became flesh" (John 1:14). This saying is as difficult to understand as it is challenging to belief. It has many layers of meaning, one of which I propose to explore. In the past, it distressed me that our discipline, which should deal in eternal verities, is more fashion-ridden than the salon of any Paris couturier. In the course of an undeservedly long life, I have lived through many fashions, from neo-Hegelian idealism through Liberalism, Neo-orthodoxy, Existentialism, Secularism, Death-of-God, and so on. I estimate that the half-life of the average theological fashion is about ten years. The ephemeral character of our theological adventures distresses me no longer. This is the sarx—-the fleshly, temporal character of all our being and doing. We do indeed attempt to express and interpret the eternal truth of God but we can do so with relevance only within the context of our own living and ever-changing situation. Certainly we need the relative permanence of the creeds as the body needs a skeleton. But skeletons without flesh belong either in the grave or in a museum. Without the flesh of contextual relevance, the ancient creeds read like strange and largely meaningless metaphysical recipes. They even give instructions on how to combine the ingredients without dividing the substance or confounding the natures, and so on.